Quantum Monte Carlo Study of the Reactions of CH with Acrolein: Major and Minor Channels - Pakhira, Srimanta; Singh, Ravi I; Olatunji-Ojo, Olayinka; Frenklach, Michael; Lester, William A (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2016)
Acrolein is an important unsaturated hydrocarbon, containing both CO and CC bonds, and responsible for atmospheric pollution. A recent study of major reactions of CH with acrolein has been supplemented with computations of other reactions of the system. Similar to the previous approach, the quantum Monte Carlo (QMC) method in the accurate diffusion Monte Carlo (DMC) method was implemented. Single determinant wave functions were used as trial functions for the random walks. Rate coefficients and product branching ratios were computed by solving master equations using the MultiWell software suite. At room temperature, the dominant product channels are 2-methylvinyl + CO (P6), 1,3-butadienal + H (P2), and furan + H (P1). At elevated temperatures, 2,3-butadienal + H (P10) is also a major product. The chain decomposition pathway to form C3H4 + HCO was not competitive with the cyclization pathway at any of the temperatures studied. The DMC branching fractions of the products formed in the subject reaction are in reasonable accord with previous experimental and theoretical values. The computed rate coefficients were found to be independent of pressure at temperatures relevant to combustion (1500–2500 K).